Draft Annual Plan 1993-94 Andhra Pradesh Volume-II (Sectoral Programmes) 5. Industry and Minerals - Planning Commission (Planning Commission, 1992)
Andhra Pradesh State is well endowed in resources for industry. The State has substantial reserves of coal, iron ore, mica, asbestos as well as natural gas and oil. The State also has large forest tracts which can be industrially exploited. It has a long coast line of a thousand kilometers providing access to marine raw materials. The State, of course, has a flourishing agriculture consisting of rice and other food grains as well as commercial crops like groundnut, castor and other oils, sugarcane, and fibres like cotton, mesta and tobacco.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh